PTU-239 EUS assessment of lesions of the ampulla of Vater: of particular value in low grade dysplasia. (28th May 2012) - Roberts, K; McCulloch, N; Mayer, D; Isaac, J; Muiesan, P; Bramhall, S; Mirza, D; Sutcliffe, R; Forde, C; Marudanayagam, R; Mahon, B
Abstract : Introduction: Lesions of the ampulla of Vater are difficult to stage using conventional cross sectional imaging and endoscopy. An accurate diagnosis is essential as this permits endoscopic resection in dysplastic lesions preserving pancreatoduodenectomy for malignant cases. Endoscopic ultrasound has greater sensitivity and specificity than conventional imaging in staging lesions. To date its role in staging dysplastic lesions is unclear. Methods: Patients with adenomas or adenocarcinomas of the ampulla were identified from departmental databases over a 5-year period. Methods of presentation, investigation, treatment and outcome were recorded. Patients with no EUS were compared to those with EUS. Results: Of 58 patients, 27 were investigated with an EUS. There was no difference in age, sex or method of presentation between groups. The preoperative diagnosis was correct in 94% of cases in the EUS group vs 61% in the no EUS group (p=0.006). The sensitivity, specificity, positive and negative predictive values in the EUS group to correctly identify malignant lesions was 93, 100, 100 and 93% respectively. For the non-EUS group these values were 77, 91, 93 and 72%. Every diagnosis of low grade dysplasia (LGD) was correct in the EUS group while these accounted for the majority of errors in the no EUS group. High grade dysplasia (HGD) was frequently understated. Conclusion: When added to existing investigations, EUS increases the accuracy of preoperative staging of ampullary lesions being particularly useful in cases of LGD. This permits safe endoscopic management of these cases. Cases of HGD must be reviewed carefully and considered for pancreatoduodenectomy. Competing interests: None declared.